Dinâmica do componente arbóreo e estrutura do estrato de regeneração da floresta estacional semidecidual da Fazenda do Glória, Uberlândia, MG - Magalhães, Júlio Henrique Ribeiro (2014)
CHAPTER I: The dynamics of a forest refers to all changes occurring over time in their structure and, through its study, we seek to find patterns of variation that reveal how the ecological succession occurs in these environments. Several dynamics studies have been carried out in different forest types since tropical rain forests until dry deciduous forests with high influence of seasonality, which revealed no stability there in the forest, as this is subject to constantly disturbance, even localized and of low intensity. The present study aimed to analyze the dynamics of a seasonal semideciduous forest, describing the changes done in the community and populations in the period out of five years, in an attempt to identify patterns of behavior to populations or groups of populations and compare the results with other studies conducted in similar formations. For this two samples were taken from 25 plots of 20 x 20 m in 2006 and in 2011,in a fragment of semideciduous forest. The data for phytosociological analysis and further dynamics analysis were collected. The results showed a decrease in species richness from 89 in 2006 to 84 in 2011. The community has shown an increase in total basal area, which was 26.33 m² / ha to 27.61 m² / ha, despite having been a decrease in the density of 976 ind / ha for 934 ind/ha. Most populations showed mortality rates and recruitment rates below the community rates. The group of shade-tolerant species had a faster dynamics compared to the group of light demanding species, for all calculated parameters. Result that is mainly due to high rates of a small group of species, all shade-tolerant, which is Siparuna guianensis, Trichilia pallida, Casearia grandiflora and Cordiera sessilis. These were the only species with mortality and recruitment above the mean of community and in said order had the highest turnovers rates. Siparuna guianensis although have a high VI to the community, showed mortality rates greater than recruitment rates, resulting in the decline of its population, which increased from 95 ind/ha in 2006 for 66 ind/ha in 2011. In the analysis with the most representative species of the community it is observed that the pioneer species are the group that is decreasing in density, with mortality greater tham recruitment. In this group there is a predominance of species with intermediate wood density and a sort of light wood. In contrast, the group of species that is increasing in density is predominantly composed of species of heavy and medium density wood, without any specie of light wood. The results point to a breakthrough in the successional stage of the forest, since this is free of recent human disturbance and natural intense, showing reduction in the number of species, reduction in the total density of individuals, including the pioneer species; increase in basal area and predominant species of higher wood density in the group with higher recruitment of than mortality. CHAPTER II: Natural regeneration is comprised of young plants that occupy the lower strata of the forest, many of which will form the future tree community. In a forest, density is inversely proportional to the size of the individuals. Thus, a high mortality rate is imposed on smaller individuals, and reach adulthood, those who find favorable environmental conditions at sites where they settled. The opening of a clearing is a major event that determines the success of different species in regeneration. The present study aims to describe the composition of natural regeneration, evaluate its structure and compare it to the tree layer. For this regenerating individuals were sampled in 50 plots of 5 x 10 m (allocated within plots where the tree layer sampling occurred) in a fragment of semideciduous forest. Were considered as part of the natural regeneration all individuals of tree species with height 1 m CAP <15 cm. The phytosociological parameters and indices of natural regeneration by height class and total for each species were calculated. 1460 individuals of 90 species were sampled in 0.25 ha of area. Siparuna guianensis and Trichilia pallida that are shade tolerant species, had the highest densities, 295 and 294 individuals, respectively, excelling in all parameters analyzed. Regarding light demanding species, Duguetia lanceolata, Astronium nelson-rosae and Aspidosperma discolor were the most outstanding, both in value of importance (VI) as total natural regeneration (RNT). Whereas the two samples of adults added to regeneration, was recorded 116 tree species, 24 exclusive of regeneration. The exclusive species of regeneration occurred at low densities, while 63% of them apresentarm maximum of three individuals. Among them, there the dominance of pioneer species, unlike that observed for the tree layer and for regeneration as a whole, where low proportions of pioneering occur. Trichilia hirta had his first record for the region and was the most abundant among the exclusive species of regeneration. The similarity index of Jaccard and Morisita (mod. Horn) showed greater similarity of regeneration (sampled in 2012) with the first sampling of the tree layer (2006), compared to the second (2011). This result can be explained by the fact that natural regeneration be reflective of the seeds dispersed in the past, which take some time to settle and reach the size of 1 m (inclusion level). The sharp decline in the value of RNC in classes with greatest height of Cardiopetalum calophyllum affected the group of early secondary species, which showed the same pattern of decline. In contrast the group of late successional species increased in value of RNC in the larger height classes. This result suggests that in layer regeneration, early secondary species are more susceptible to mortality. The absence of Ocotea corymbosa in regeneration, coupled with his mortality and no recruitment among the trees layer, indicates that, although it is the most important specie of tree community,should disappear of the area, being replaced by Duguetia lanceolata, Astronium nelson-rosae and Aspidosperma discolor that has been highlighted in both the tree layer as in regeneration, have wood density greater than O. corymbosa and belong to the same layer.